Informing the Symptom Profile of Complicated Grief - Simon, Naomi M. (2010)
BACKGROUND: Complicated Grief (CG) is under consideration as a new diagnosis in DSM5. We sought to add empirical support to the current dialogue by examining the commonly used Inventory of Complicated Grief (ICG) scale completed by 782 bereaved individuals. METHODS: We employed IRT analyses, factor analyses, and sensitivity and specificity analyses utilizing our full sample (n=782), and also compared confirmed CG cases (n=288) to non-cases (n=377). Confirmed CG cases were defined as individuals bereaved at least 6 months who were seeking care for CG, had an ICG ≥ 30, and received a structured clinical interview for CG by a certified clinician confirming CG as their primary illness. Non-cases were bereaved individuals who did not present with CG as a primary complaint (including those with depression, bipolar disorder, anxiety disorders and controls) and had an ICG<25. RESULTS: IRT analyses provided guidance about the most informative individual items and their association with CG severity. Factor analyses demonstrated a single factor solution when the full sample was considered, but within CG cases, six symptom clusters emerged: 1) yearning and preoccupation with the deceased, 2) anger and bitterness, 3) shock and disbelief, 4) estrangement from others, 5) hallucinations of the deceased, and 6) behavior change, including avoidance and proximity seeking. The presence of at least one symptom from three different symptom clusters optimized sensitivity (94.8%) and specificity (98.1%). CONCLUSIONS: These data, derived from a diverse and predominantly clinical help seeking population, add an important perspective to existing suggestions for DSM5 criteria for CG.